Surfing the Waves of Globalization: Asia and Financial Globalization in the Context of the Trilemma - Joshua Aizenman; Menzie D. Chinn; Hiro Ito (Asian Development Bank (ADB), 2009)
Using the "trilemma indexes" developed by Aizenman et al. (2008) that measure the extent of achievement in each of the three policy goals in the trilemma - monetary independence, exchange rate stability, and financial openness - this paper examines how policy configurations affect macroeconomic performances with focus on the Asian economies. We find that the three policy choices do not matter for per capita economic growth. However, they do matter for output volatility and the medium-term level of inflation. Greater monetary independence is associated with lower output volatility while greater exchange rate stability implies greater output volatility, which can be mitigated if a country holds international reserves (IR) at a higher level than a threshold (about 20% of gross domestic product). Greater monetary autonomy is associated with a higher level of inflation while greater exchange rate stability and greater financial openness could lower the inflation level. We find that trilemma policy configurations and external finances affect output volatility mainly through the investment channel. While a higher degree of exchange rate stability could stabilize the real exchange rate movement, it could also make investment volatile, though the volatility-enhancing effect of exchange rate stability on investment can be cancelled by holding higher levels of IR. Greater financial openness helps reduce real exchange rate volatility. These results indicate that policy makers in a more open economy would prefer pursuing greater exchange rate stability and greater financial openness while holding a massive amount of IR. Asian emerging market economies are found to be equipped with macroeconomic policy configurations that help the economies to dampen the volatilities in both investment and real exchange rate. These economies' sizeable amount of international reserves holding appears to help enhance the stabilizing effect of the trilemma policy choices, which explains the recent phenomenal buildup of international reserves in the region.
hdl:11540/1833
Keywords: 330; trilemma policy; Asian emerging market economies; financial globalization; output volatility; Globalisierung; Geldpolitik; Wechselkurs; Finanzmarktregulierung; Wirkungsanalyse; Bruttoinlandsprodukt; Volatilität; Schwellenländer; Asien